2012
DOI: 10.1177/1934578x1200700910
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Anti-angiogenic Activity of Saponins from Maesa lanceolata by Different Assays

Abstract: Angiogenesis, in which a vascular network is established from pre-existing vessels, is a complex multistep process. Mechanisms underlying angiogenesis can be investigated using a variety of in vitro, ex vivo and in vivo approaches. Evaluation of several promising plants and plant metabolites, including terpenoids, revealed promising anti-angiogenic activity. Since the maesasaponins displayed anti-angiogenic activity in the chick chorioallantoic membrane (CAM) assay, their activity was further investigated in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Therefore, the synergistic combinations can be used for advanced drug delivery purposes. Anti-angiogenesis activity along with CAM assay has also been used to study the action of nano-particles on blood vessels formation (Foubert et al, 2012). The formation of wide, thick vascular zones indicates the anti-angiogenic activity of F4 nanoparticles on the blood vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the synergistic combinations can be used for advanced drug delivery purposes. Anti-angiogenesis activity along with CAM assay has also been used to study the action of nano-particles on blood vessels formation (Foubert et al, 2012). The formation of wide, thick vascular zones indicates the anti-angiogenic activity of F4 nanoparticles on the blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…An anti-angiogenesis activity was conducted using the chick chorioallantoic membrane (CAM) assay (Foubert et al, 2012). The 7-d-old fertilized eggs were purchased, disinfected with 70% ethanol, and transferred to an incubator (GENEI, Bangalore, India) at 37 C with 75% humidity; they were kept in these optimal growth conditions for 24 h. To ensure equal distribution of the blood vessels, the eggs were turned over every 6 h. After 24 h, the eggs were wiped with ethanol (70%) to prevent any mild infections, and then the eggshells were sawed with a metal saw blade.…”
Section: Blood Compatibility Studiesmentioning
confidence: 99%
“…As THBS1 is known to be a protein exhibiting anti-angiogenic activity 26 , 27 , and anti-angiogenic activity has been established in the soybean isoflavone, genistein 44 , 45 . In addition, anti-angiogenic activity of soy saponins has also been reported 46 . As shown in Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The structure–activity relationship studies of Pulsatilla saponins showed that the presence of the carboxyl group at the C-28 position was necessary for the anti-cancer activities of these saponins, although it increased their hemolytic effects [ 204 , 205 , 206 , 207 , 208 ]. Platycodin D ( Figure 5 ) [ 209 , 210 ], julibroside J8 [ 211 ], maesasaponins (I-VII.1) [ 212 ], astragaloside IV [ 213 ], capilliposide B ( Figure 5 ) [ 214 ], raddeanin A ( Figure 5 ) [ 215 , 216 ], and gleditsiosides B [ 217 ] are other triterpenoid saponins with anti-angiogenesis activities described in Table 1 . Triterpenoid saponins showed anti-angiogenesis activities via blocking the pro-angiogenesis mediators, including VEGF and HIF-1α, as well as suppressing the PI3K/Akt, MAPKs, and NF-κB as stimulation angiogenesis cellular signaling pathways.…”
Section: Saponinsmentioning
confidence: 99%